Penguatan Kapasitas Pemuda Negeri Rumahtiga Terkait Polemik Penetapan Matarumah Parentah - Tita, Heillen Martha Yosephine; Mustamu, Julista; Irham, Muhammad (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Youth in Rumahtiga State, as one of the backbones of the country's development, which actually has direct contact with the country's government, is a potential resource to encourage the government in running the government. For this reason, this service is considered important to carry out, in order to provide legal understanding for the community, especially the Youth of Rumahtiga State, regarding the importance of the responsibilities and contributions of Youth in the field of State Government as well as the role of youth in the Parentah House Polemic in Rumahtiga State.Purposes of Devotion: Providing capacity strengthening to Rumahtiga Youth in relation to responsibility towards the State in terms of the Determination of Parentah House Points, which is still a polemic.Method of Devotion: The method used is in the form of group discussions involving youth groups in several youth organizations in Rumahtiga.Results of the Devotion: From the presentation of the material, and several questions and discussions, it was found that so far youth groups in Rumahtiga State have not been accommodated enough to contribute in the field of government, regarding the equal role of youth in the Parentah House Polemic in Rumahtiga State which is resolved in the realm of law is the right step.